Evaluation of the effectiveness of the use of case-technology in teaching computer modeling of future teachers of informatics - Olga S. Markovich; Alexey N. Sergeev (RUDN Journal of Informatization in Education, 2019)
Problem and goal. The article describes the problem of using case-technology in teaching computer modeling to future teachers of informatics. The relevance of solving this problem is determined by the need to find new approaches to combining the fundamental and applied training of future teachers in order to form a holistic competency that provides a solution to professional pedagogical problems. The purpose of this study was to design a model of training future teachers of informatics in the field of computer modeling using case-technology, as well as testing this model during a pedagogical experiment. Methodology. The basis of the developed methodological approach was the use of subject-oriented cases in teaching computer modeling to future teachers of informatics. This type of cases is considered as a set, which includes: 1) situational problem; 2) tasks, the implementation of which leads to the solution of the problem; 3) materials needed to complete tasks; 4) software tools for solving the problem. The model of training of future teachers of informatics using case-technology is considered as a set of target (formation of competence of the teacher of informatics in the field of computer modeling), content (the content of the course “Computer Modeling”) and process components (three stages of design, development and direct application of the subject-oriented case of computer modeling in the classroom). To assess the effectiveness of the case-technology application, a pedagogical experiment was conducted, involving the implementation of training in experimental and control groups. Results. The article presents the results of an experiment conducted at the Volgograd State Socio-Pedagogical University. During the experiment in the control and experimental groups, a course of computer modeling was implemented with the preservation of the content, but with the use of case-technology in the experimental group. Criterion evaluation of the effectiveness of the formation of competence of the teacher of informatics in the field of computer modeling was carried out in the subject and research aspects. The results of the experiment showed that in the experimental groups increased the number of students represented at high, as well as medium and high levels of formation of both the subject and research component of the competence. Conclusions. The study showed that the proposed approach to the use of case-technology provides high results. The obtained and statistically confi data of the experiment allow us to speak about the effectiveness of the use of case-technology as a means of teaching computer modeling to future teachers of informatics.